Peningkatan Kualitas Lingkungan pada Permukiman Tradisional (Studi Kasus di Desa Panglipuran dan Desa Tenganan di Provinsi Bali dan di Dusun Sade serta Desa Senaru di Provinsi NTB) - Muhajirin, Muhajirin (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
The improvement of traditional neighborhoods is a way to make the neighborhoods clean, organized and healthy. The existing conditions of traditional neighborhoods in general are such as the unarranged road environment, which many of them are still dirt roads, the unavailability of adequate clean water infrastructure, household wastewater treatment infrastructure, drainage (rainwater channels), solid waste transfer station, including the unavailability of supporting facilities in traditional neighborhoods such as firefighting infrastructure. Furthermore, the purpose of this study was to assess the availability or condition level of the existing public works infrastructure and facilities at the traditional neighborhoods in Panglipuran and Tenganan Village in Bali and Sade Hamlet and Senaru Village in NTB Province associated with the Minimum Service Standards (MSS) of Public Works and Spatial Planning issued by the Minister of Public Works No.14/PRT/M/2010, dated 25 October 2010 on Minimum Service Standards Sector of Public Works and Spatial Planning. The method used is descriptive comparative method that compares the Regulation of Minister of Public Works concerning Minimum Standards of Public Affairs with the condition of the existing infrastructure and facilities in some traditional neighborhoods in Bali and NTB. The result of some traditional neighborhoods in Panglipuran and Tenganan Village in Bali and in Sade Hamlet and Senaru Village in West Nusa Tenggara Province compared to the MSS of public works that must be met by traditional neighborhoods concluded that there are some traditional neighborhoods that already provided full required infrastructure (Panglipuran village), has met most of them (Village Tenganan), just built neighborhood road infrastructure (Sade Hamlet) and has not provided roads, clean water, waste water, solid waste and drainage infrastructures and facilities at all (Senaru Village) .